T-cell subsets are associated with serum homocysteine concentration in patients with essential hypertension - Huifeng Xu; Huan Zheng; Junling Huang; Yi Shen; Ming Luo (Clinical and Experimental Hypertension, 2017)
Objective: To explore the association between serum homocysteine (Hcy) concentration and T-cell subsets from patients with essential hypertension. Patients and Methods: A total of 218 essential hypertension patients were recruited, of which 170 were H-type essential hypertensive and 48 were non-H-type essential hypertensive. H-type essential hypertensive patients were divided into three groups by concentration of serum Hcy. The peripheral blood T-cell subsets (CD3+%, CD4+%, CD8+ T%, CD4+/CD8+) and clinical features including age, sex, serum creatinine, uric acid, total cholesterol, triglycerides, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were recorded and analyzed with T-cell subsets which were counted by fluorescence activated cytometry. Results: Compared with non-H-type hypertensive patients, CD4+ T-cell percentage in peripheral blood was significantly decreased in H-type hypertensive patients. Because of the increase of Hcy level, CD4+ T-cell percentage decreased. Linear regression analysis showed that Hcy level was negatively correlated with CD4+ T-cell percentage; however, it was positively correlated with CD3+ T-cell percentage. Conclusion: A direct association between serum Hcy concentrations and T-cell percentage was observed in patients with essential hypertension. This observation indicates that T-cell subsets might play an important role in hypertension.